Amyloid protofibril is highly voluminous and compressible - Akasaka, Kazuyuki; Latif, Abdul Raziq Abdul; Nakamura, Akihiro; Matsuo, Koichi; Tachibana, Hideki; Gekko, Kunihiko (Biochemistry (Easton), 2007)
We report here results of the first direct measurement of partial volume and compressibility changes of a protein as it forms an amyloid protofibril. We use a high precision density meter and an ultrasonic velocity meter on a solution of intrinsically denatured, disulfide-deficient variant of hen lysozyme, and follow the time-dependent changes in volume and compressibility, as the protein spontaneously forms a protofibril. We have found a large increase in partial specific volume with time from 0.684 to 0.724 mL x g-1 (Deltanu = 0.040 mL x g-1 corresponding to 570 mL x (mol monomer)-1) and in partial specific adiabatic compressibility coefficient from -7.48 x 10(-12) to +1.35 x 10(-12) cm2 x dyn-1 (Deltabetas = 8.83 x 10(-12) x cm2 x dyn-1) as the monomer transforms into a protofibril. The results demonstrate that the protofibril is a highly voluminous and compressible entity, disclosing a cavity-rich, fluctuating nature for the amyloid protofibril. The volume and compressibility changes occur in two phases, the faster one preceding the major development of the beta-structure in the protofibril as monitored by CD.